Coloring complex shapes decreases patient anxiety in three care environments: a pilot study with color analysis - Dias Alves, Manuel; Olmi, Elodie; Durand, Jean-Yves; Mitri, Fabien; Knefati, Yannick; Vion-Dury, Jean (Frontiers in Psychology, 2024)
This study was conducted to determine the effectiveness of coloring activity of circular symmetrical shape with complex patterns, so-called mandala, on anxiety associated with chronic illness in 3 different ambulatory medical situations (general consultation, psychiatric day hospital, hemodialysis session).Thirty patients were included in 3 groups and came from 3 different ambulatory medical situations: a hemodialysis group (n=10), a psychiatric day hospital group (n=10) and a nephrology consultation group (n=10). We asked the patients to fill STAI-S and STAI-T questionnaires before to color complex circular shape with complex patterns, then to fill the STAI-S questionnaire again and a questionnaire on the experience of the activity.The results show that the STAI-S score was significantly lower after coloring for the hemodialysis (p=0.02) and psychiatric groups (p=0.005) but not for the general consultation group (p=0.26). STAI-T scores did not differ between groups. The distribution of colors in the mandala was different in the 3 groups of patients. A positive subjective experience of the activity was found in all groups.These results show the effectiveness of a coloring activity of a circular shape with complex patterns on anxiety associated with chronic illness in care environment. The different distribution of the colors of the mandala in the 3 groups raises the question of the influence of the context on the mood of the patients and the deeper meaning of the choice of colors and their placement in the mandala. Our study reinforces the multiple applications of art activities in different medical disciplines and encourages their development within healthcare settings.